2011
DOI: 10.1111/j.1537-2995.2011.03066.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fibrinogen measurement methods with fibrin clot elasticity assessed by thromboelastometry, before and after administration of fibrinogen concentrate in cardiac surgery patients

Abstract: Agreement between fibrinogen concentration measurement methods decreased considerably after fibrinogen concentrate administration. All methods correlated acceptably with FIBTEM MCF at the end of CPB, but not after hemostatic therapy. Further investigation is needed to explain these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 48 publications
7
67
0
1
Order By: Relevance
“…Firmness of the fibrin-based clot is measured in SI units (Système International d'Unités) that are completely different from those of fibrinogen concentration (dyne/cm 2 or gigapascal, PERIOPERATIVE MEDICINE as opposed to g/l or mol/l). 32 Nevertheless, studies have shown correlation between FIBTEM MCF and measurements of fibrinogen concentration. 13,22 The aim was to restore FIBTEM MCF to 22 mm, higher than the mean preoperative baseline level of 16-18 mm and at the high end of the normal range (9-25 mm).…”
Section: Fibrinogen Concentrate Therapy In Aortic Surgerymentioning
confidence: 99%
“…Firmness of the fibrin-based clot is measured in SI units (Système International d'Unités) that are completely different from those of fibrinogen concentration (dyne/cm 2 or gigapascal, PERIOPERATIVE MEDICINE as opposed to g/l or mol/l). 32 Nevertheless, studies have shown correlation between FIBTEM MCF and measurements of fibrinogen concentration. 13,22 The aim was to restore FIBTEM MCF to 22 mm, higher than the mean preoperative baseline level of 16-18 mm and at the high end of the normal range (9-25 mm).…”
Section: Fibrinogen Concentrate Therapy In Aortic Surgerymentioning
confidence: 99%
“…The maximum clot fi rmness, or maximum amplitude, is measured after a defi ned time. The results are not only dependent on the fi brinogen concentration, but may be infl uenced by hematocrit, FXIII, heparin, hydroxyl-ethyl starch, gelatin, and albumin (Solomon et al 2011 ;Ogawa et al 2012 ;Schlimp et al 2013 ). None of these tests is standardized, and the international, gold standard test is currently debated.…”
Section: Monitoringmentioning
confidence: 96%
“…Neither test is a suitable substitute for the traditional plasma-based determination of fi brinogen levels using the Clauss method. Furthermore, the correlation between FIBTEM MCF and the plasmatic concentration of fi brinogen worsens after exogenous fi brinogen administration (Solomon et al 2011 ).…”
Section: 6mentioning
confidence: 99%